Hitler's fatal miscalculation : why Germany declared war on the United States - Schmider, Klaus 1966- (Cambridge military histories, 2021)
"In the last days of November 1941, Nazi Germany's strategic situation was ambiguous: her armies were in possession of most of continental Europe and fighting deep inside the USSR, but the momentum of the Wehrmacht's war machine appeared to be spending itself. In relation to the numbers of U-boats available, sinkings had been dropping since June; her surface fleet was unlikely to pick up the slack, since it had just had fuel restrictions imposed on it which all but ruled out a resumption of Atlantic operations. In the air, nighttime RAF bombing raids were becoming a feature of everyday life, and reaching deeper and deeper into areas of the German geography thus far untouched. On the Russian front, which consumed most of the army's and air force's assets, operations aimed at rendering the situation of the defenders of Leningrad and Moscow untenable and force the surrender of those of Sevastopol, were still in progress. On the downside, Army Group South had just been forced to abandon its most recent prize - the city of Rostov - to the counterattacking Red Army, an event that definitely had to be rated as a 'first' in the annals of the Russo- German war. Crucially, the war economy which needed to deliver a maximum output if the armed forces of the Third Reich were to have even a remote chance of meeting the conflicting priorities set by their warlord, had entered a period of crisis, with neither enough labour nor raw materials available to meet the demands for 1942"--